Причини та умови, які сприяють поширенню та вчиненню правопорушень у сфері обігу наркотичних засобів із залученням неповнолітніх - Хитра, О. Л.; Хитрая, О. Л.; Hitraja, O. (Одеса : Юрид. л-ра, 2014)
This paper examines current issues related to the establishment of the causes and conditions conducive to the spread and offenses related to drugs involving minors. Based on statistics and analysis of the drug situation in the country proved that one of the factors involved in the interaction of causes and conditions for the offense of narcotic drugs involving minors, is generated by other system processes and phenomena that contribute to the occurrence and impact on drug offenses state of law and order in the state.
Хитра О. Л. Причини та умови, які сприяють поширенню та вчиненню правопорушень у сфері обігу наркотичних засобів із залученням неповнолітніх / О. Л. Хитра // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 359-365.
Keywords: залучення; неповнолітні; наркоправопорушення; попередження; протиправність; привлечение; несовершеннолетние; наркоправонарушения; предупреждения; противоправность; attraction; minors; drug crimes; warning; wrongfulness